2007
DOI: 10.1159/000099006
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Hyperparathyroidism Is Associated with Higher Cost of Care among Chronic Kidney Disease Patients with Cardiovascular Comorbidities

Abstract: Background: Chronic kidney disease (CKD) is associated with high morbidity and mortality, and incurs a substantial cost. Secondary hyperparathyroidism (SHPT) is a major complication associated with CKD and has been linked with cardiovascular disease, leading to poor outcomes. Methods: We analyzed retrospective studies for the prevalence of congestive heart failure (CHF) and acute myocardial infarction/ischemic heart disease (AMI/IHD) in pre-dialysis CKD patients to estimate the additional hospitalization cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
1
13
1
1
Order By: Relevance
“…As noted above, studies in CKD patients in the US by Schumock et al [17] and Khan et al [18] have previously shown that SHPT can substantially increase healthcare costs. Results of these US studies are not directly comparable to ours due to patients’ different CKD stages at baseline and the focus on patients with diabetes by Schumock et al [17] and on those with CVD by Khan et al [18].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As noted above, studies in CKD patients in the US by Schumock et al [17] and Khan et al [18] have previously shown that SHPT can substantially increase healthcare costs. Results of these US studies are not directly comparable to ours due to patients’ different CKD stages at baseline and the focus on patients with diabetes by Schumock et al [17] and on those with CVD by Khan et al [18].…”
Section: Discussionmentioning
confidence: 95%
“…Total healthcare costs were 320% higher in diabetic CKD patients with SHPT compared with those without SHPT [17]. Khan et al [18] estimated the cost contribution of elevated iPTH levels in CKD patients in the US with congestive heart failure (CHF), all in stages prior to ESRD at baseline. Patients with iPTH ≥ 65 pg/mL had US$205 higher mean monthly CHF-related hospitalisation costs (in 2005 US$) in the period 1 to 3 months preceding dialysis compared with patients with iPTH < 65 pg/mL (below the upper bound of the K/DOQI target range for patients with Stage 3 CKD: 35–70 pg/mL [5]).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, our study is the first to evaluate the association of secondary hyperparathyroidism with hospitalization. The association of secondary hyperparathyroidism with mortality is well established in chronic renal failure patients [15][16][17][18][19] . A previous Australian study conducted with institutionalized elderly adults living in geriatric institutions and clinics also showed the 1 The GFR was calculated using the Cockcroft-Gault equation [25].…”
Section: Discussionmentioning
confidence: 99%
“…What we do not know is whether the correction of secondary hyperparathyroidism by supplementing calcium and vitamin D would prevent hospitalization. In patients with chronic renal failure, the decrease in serum PTH levels improves the prognosis of the patients, and the correction of hyperparathyroidism associated with vitamin D deficiency reduces the number of falls and fractures [15,16] . These data suggest that the reduction in serum PTH levels, possibly below 48 pg/ml, may have an impact on the health of the elderly population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation